Issues of criteria normalization in the multicriteria analyzes in the design of roads - Żabicki, Piotr; Gardziejczyk, Władysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Multicriteria analysis is a method for supporting the decision process in a situation where there are many variants of road alignments analyzed during the preparation of project documentation of motorways, expressways and bypasses. It is based on an appropriate choice of assessment criteria and weights assigned to them. The aim of the multicriteria analysis is choose the most beneficial variant for road alignment from the point of view of transport, environmental, economic and social criteria. The criteria adopted for the multicriteria analysis can be expressed by using measurable or immeasurable parameters. In order to be able to compare and assess the variants, dimensionless quantities must be assigned to the all criteria. The process of replacing a dimension quantity with a dimensionless one is called normalization. Normalization may be performed on the basis of maximizing the variables (stimulants) or to minimize the variables (destimulants). The analyses presented in the article examine the impact of the adopted method of criteria normalization and the weights of the criteria used for the selection of a road variant.